(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Scholarly literature has looked into nascent democracies and public administration in developing countries. However, the link between public administration institutions and sustainability of new democracies in developing countries, especially countries with ancient traditions of public administration, has not been fully explored. This paper argues that the institution of district magistracy is better suited to improve the levels of instrumentation and protracted consultation in the country and hence better able to sustain its democracy.Modern democratic system is the most appropriate system from the point of view of good governance. With reference to western democracies, it may be opined that they are very near the models of good governance, but in developing countries like India they are still far from the goal of good governance. Indian democratic structure of governance, which is the largest democracy of the world, achieved good level during the last six and half decades.